Nordisk samarbejde omkring børnelitteratur - institutioneile rammer og konkrete tiltag - Haber-Biały, Justyna (Folia Scandinavica Posnaniensia, 2007)
The author presents main institutions and ideas concerning the Nordic cooperation within children’s literature. The Nordic culture-model is analyzed with focus on children’s fiction. The paper includes some reflections about the Danish way of circulation of children’s literature in Denmark and examines cooperation strategies in Nordic countries.